Mineral orgânico na alimentação de poedeiras comerciais criadas em sistema cage free - Silva, Nayara Emanoelle Matos e (2024)
The production of commercial eggs for consumption has grown considerably in recent years around the world. Poultry farming is composed of pillars that involve the breeding system, laying hen genetics, health and nutrition. The present work was carried out in the research aviary of the Experimental Farm of Animal Science and Agronomy at UFMT - Campus Cuiabá. The design used was completely randomized with 4 treatments, as follows: control diet with 100% calcitic limestone (50% bran and 50% fine), T2 diet with 83.9% calcitic limestone + 16.1% limestone based on Lithothamnium sp. Bran, T3 feed with 83.9% calcitic limestone + 16.1% limestone based on Lithothamnium sp. in powder form, T4 ration with 83.9% calcitic limestone + 8.05% limestone based on Lithothamnium sp. bran + 8.05% limestone based on Lithothamnium sp. in powder. 140 birds of the commercial lineage Novogen Brown with 28 weeks were used, with 7 replications, totaling 28 experimental units, with 5 birds each. The total collection period was 63 days divided into three cycles of 21 days. The performance parameters of the birds were evaluated: weight gain g/bird/day (GP), feed intake g/bird/day (CR), feed conversion (CA), feed conversion per dozen eggs (CADO), conversion feed by egg mass (CAMO), and egg production (PO) and internal and external egg quality: specific gravity (GE), average egg weight (PMO), haugh unit (UH), yolk index (GI), weight of yolk, shell and albumen components (PC/g), percentage of yolk, shell and albumen components (PC/%), shell thickness (EC). The objective of carrying out this research was to evaluate the performance and quality of eggs from commercial laying hens in a Cage Free rearing system, supplemented with diets with the inclusion of organic minerals (calcareous algae) in different particle sizes (mashed and powdered form). There was a significant effect (p<0.05) for the variables albumen thickness, shell weight, specific gravity, percentage of shell, percentage of albumen, albumen height, feed intake and bird weight gain. Improved feed intake and bird weight gain were observed, as well as improvements in egg quality, albumen thickness, shell weight, shell percentage, albumen percentage, albumen height. Organic limestone alternatives (calcareous algae) in different granulometries need to be studied for definitions of the best levels and granulometric form.